Multicultural Islamic Education as Conflict Resolution for Multi-Ethnic and Religious Communities in Polagan Galis Pamekasan - Ach Sayyi; Imaniyatul Fathriyah; Zainullah Zainullah; Shahibul Muttaqien Al-Manduriy (Universitas Islam Lamongan, 2022)
This study aims to uncover the phenomenon of multi-ethnic and religious communities that can coexist despite different ethnicities, ethnicities, races, and even different religions. The phenomenon is relatively rare, considering that this community is located in Madura which is identical to the streotype that depicts a violent, fierce and even cruel society. This study used qualitative-discrete methods with a type of realist-autoethnographic. The approach used is an interdisciplinary approach. Data analysis used is a spiral of analysis, namely message data, read and create memos, analyze, classify, describe, present and visualize. The results showed that there are two aspects of the findings; First, the values of Islamic education that are embedded and developed in multi-ethnic and religious communities so that they can coexist without conflict, namely the value of knowing each other, understanding each other, helping value, moderate, harmony, diversity, equality and justice, deliberation, and brotherhood value; Second, the praxis of multicultural Islamic education as a conflict resolution of multi-ethnic and religious communities in the village of Polagan is a manifestation of the instillation of these values through several processes or approaches and strategies that are implemented naturally and independently, namely Transformation process, the process of inculcation and social capital approach.